1987
DOI: 10.1042/cs0720373
|View full text |Cite
|
Sign up to set email alerts
|

Lung lavage fluid from patients with α1-proteinase inhibitor deficiency or chronic obstructive bronchitis: anti-elastase function and cell profile

Abstract: The anti-elastase composition of bronchoalveolar lavage (BAL) fluid from alpha 1-proteinase inhibitor (alpha 1PI) deficient and bronchitic patients was determined by immunological and functional assays, together with the cell profile of the BAL fluid. alpha 1PI, anti-leucoprotease and alpha 2-macroglobulin were present in all the samples BAL fluid alpha 1PI concentrations were significantly lower in the group with serum alpha 1PI deficiency. Lavage fluid from alpha 1PI deficient subjects inhibited less porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 0 publications
4
56
0
4
Order By: Relevance
“…In exacerbations requiring ventilatory support, only 15% of cases were associated with positive identification of a viral pathogen, and half of these were also associated with a concomitant bacterial infection, suggesting that viruses are less important in more severe exacerbations (142). Pathogenic bacterial organisms are found in 50 -80% of patients during exacerbations (143,144), with the most common organisms being Streptococcus pneumoniae, nontypable Haemophilus influenzae and Moraxella catarrhalis (19,145). Less frequently, gram negative organisms are isolated, including pseudomonas aeruginosa (146).…”
Section: Exacerbations Of Chronic Bronchitismentioning
confidence: 99%
“…In exacerbations requiring ventilatory support, only 15% of cases were associated with positive identification of a viral pathogen, and half of these were also associated with a concomitant bacterial infection, suggesting that viruses are less important in more severe exacerbations (142). Pathogenic bacterial organisms are found in 50 -80% of patients during exacerbations (143,144), with the most common organisms being Streptococcus pneumoniae, nontypable Haemophilus influenzae and Moraxella catarrhalis (19,145). Less frequently, gram negative organisms are isolated, including pseudomonas aeruginosa (146).…”
Section: Exacerbations Of Chronic Bronchitismentioning
confidence: 99%
“…Peripheral blood monocytes in the circulation migrate through blood vessel walls into various organs and differentiate into macrophages. Macrophages are the predominant effector cell in the normal lung and are increased in conditions associated with chronic inflammation, such as chronic obstructive pulmonary disease and AATD-related emphysema (23,24). It has been shown that monocytes from cystic fibrosis (CF) patients are intrinsically abnormal in their cytokine responses (25), and that this can be rescued by treatment with agonists designed to prevent DF508 cystic fibrosis transmembrane regulator (CFTR) degradation by ERAD and increase CFTR secretion (26).…”
mentioning
confidence: 99%
“…13 This conformational transition inactivates a 1 -antitrypsin as a proteinase inhibitor, thereby further reducing the already depleted levels of a 1 -antitrypsin that are available to protect the alveoli. (iii) Intrapulmonary polymers are chemotactic for human neutrophils in vitro, 14 and this may explain the finding that patients with Z a 1 -antitrypsin deficiency have an excess number of neutrophils in bronchoalveolar lavage 15 and in tissue sections of lung parenchyma. 6 The relative contribution of each of these pathways to lung damage in any given patient is unknown.…”
Section: Epidemiologymentioning
confidence: 99%